ANALISIS FINANCIAL DISTRESS PADA PERUSAHAAN PROPERTY & REAL ESTATE YANG TERDAFTAR DI BEI PERIODE 2016-2020 - Yuda Bramantha, I Wayan Swastika; Yadnyana, I Ketut (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.11.NO.03.TAHUN.2022DO - 10.24843/EEB.2022.v11.i03.p06, 2022)
The purpose of this study is to find out how the potential financial difficulties of property & real estate companies on the IDX for the 2016-2020 period are based on the Altman Z-Score, Springate and Zmijewski methods. The population in this study are the top property & real estate companies on the IDX for the 2016-2020 period. The sample was selected as many as 5 companies with a number of observations for 5 years. The analytical technique used is the Altman Z-Score, Springate and Zmijewski methods. The results show how the potential for financial distress (financial distress) for property & real estate companies based on the Altman Z-Score, Springate, and Zmijewski methods for 5 years. By using the Altman Z-Score method, the results showed that there were no companies experiencing financial distress. While using the Springate method, it was found that all companies experienced financial distress. And for the Zmijewski method, the results show that there are no companies experiencing financial distress.